Functionalized reduced graphene oxide (fRGO) for removal of fulvic acid contaminant. Issue 35 (19th April 2017) - Ray, Soumya Kanta; Majumder, Chanchal; Saha, Prosenjit
Abstract : Iron-functionalized reduced graphene oxide (fRGO)-coated sand was used for the adsorption of natural organic matter, such as fulvic acid (FA), from synthetic water. Abstract : Iron-functionalized reduced graphene oxide (fRGO)-coated sand was used for the adsorption of natural organic matter, such as fulvic acid (FA), from synthetic water. A novel synthesis route was achieved to prepare an fRGO nanocomposite. FTIR, optical microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) were applied to investigate the morphologies and structures of fRGO. Removal kinetics (pseudo-second order) and adsorption isotherms (Langmuir and Freundlich) were investigated in terms of adsorbed total organic carbon (TOC) of FA to evaluate the removal rate and adsorption capacity. The effects of pH of the FA solution and the adsorbent dose (0.5–2.5 mg g −1 ) of fRGO were further evaluated for the determination of a possible removal mechanism. A comparative study of the adsorption efficiency of fRGO and powder activated carbon (PAC) was also carried out, and the results indicated a higher FA adsorption efficacy for fRGO. The π–π interaction between the carbon atoms of FA and fRGO and electrostatic interaction between iron and functional radicals of FA were responsible for the removal.